BJPsych Bulletin author mentoring scheme –helping trainees become published authors. (February 2016) - Pimm, Jonathan; Galbraith, Niall
Summary: The publishing world is changing rapidly. Innovations include the move to open access, the rise of social media and the transition to digitalisation. In the light of these developments and with ever-increasing pressures on early career psychiatrists and trainees to publish papers in journals with a recognised pedigree, the BJPsych Bulletin is piloting an author mentoring scheme. Mentors will help clinicians and aspiring academics develop articles from a pedestrian manuscript to one that will hopefully provoke important debate and aid changes in current practices. The scheme will run on a trial basis for approximately 12 months and will then be reviewed. Mentoring has been found to have an important effect of research output including publication and grant success; the hope is that this new initiative at the BJPsych Bulletin will result in such dividends to all involved.